Pengembangan Kompetensi Siswa dalam Menulis Berita - Muhammad Rapi; Sultan Sultan; Muh Bahly Basri; Muhammad Ilham; Muh Syukri Gaffar (Universitas Muhammadiyah Sidenreng Rappang, 2024)
Journalistic activities are very important to be developed in schools to enhance students' creativity. This is in line with the era of information technology advancement that provides accessibility to users including students to produce news. The ease of producing news needs to be accompanied by the ability to write. Journalism is one of the platforms for students to develop writing skills so that it can accommodate the emergence of citizen journalism or citizen reporters who can play an active role in collecting, selecting, and reporting information that has news value. Journalism training helps students develop effective communication skills, critical of the information obtained. The training was attended by 20 participants. The training was divided into three sessions, each discussing basic journalistic concepts, news writing techniques, and news editing. Participants followed all stages of the training which was divided into three sessions. In addition to understanding journalistic theory, participants also practiced writing news. Before the training was conducted, there were three categories of participants, namely (a) students who had never participated in journalism training, (b) students who had participated in journalism training, but had never produced news, and (c) students who had participated in journalism training and had experience making news scripts. After the training was conducted, the category of students who had participated in journalism training and were able to produce news scripts.